A study on respiratory problems and pulmonary function indexes among cement industry workers in Mashhad, Iran - Ehsan Rafeemanesh; Ashkan Alizadeh; Lahya Afshari Saleh; Hosein Zakeri (Nofer Institute of Occupational Medicine, 2015)
Background: The respiratory system is the most vulnerable system in the cement industry. This study was conducted to determine the effects of occupational exposure to cement dust on the respiratory system more thoroughly. Material and Methods: In this cross sectional study an interviewer-administered questionnaire on socio-demographic characteristics and respiratory symptoms was completed and pulmonary function tests were carried out on 100 exposed and 120 non-exposed workers at the cement factory in Mashhad, Iran. The data was statistically analyzed by SPSS 16. Results: The mean of age and work duration in the exposed group was 37.5±6.3 and 10.7±5.4 years compared with the non-exposed group that was 36.1±7.1 and 10.1±5.7 years, respectively. Levels of exposure to inhalable cement dust in the exposed group were 23.13 mg/m3 (higher than national occupational exposure limits for such particles). Among the exposed group, respiratory symptoms as cough (6% vs. 0.8% of the non-exposed) and sputum (7% vs. 0.8% of the nonexposed) were significantly more prevalent (p < 0.05). Forced expiratory flow 25-75% (FEF25-75%) was significantly lower in the exposed workers compared with non-exposed ones (p < 0.05). Also forced expiratory volume in 1 s / forced vital capacity (FEV1/FVC) and FEF25-75% had a reverse correlation with the length of employment (p = 0.000 and p = 0.003, respectively). Conclusions: The findings of this study showed that occupational exposure to cement dust could be a significant factor of respiratory system dysfunction. Strict implementation of a respiratory protection program is recommended in cement industries. Med Pr 2015;66(4):471-477